A Conceptual Framework for Continuing Medical Education and Population Health. Issue 5 (20th October 2022) - Sud, Abhimanyu; Hodgson, Kate; Bloch, Gary; Upshur, Ross
Abstract: Issue: Health systems have been increasingly called upon to address population health concerns and continuing medical education (CME) is an important means through which clinical practices can be improved. This manuscript elaborates on existing conceptual frameworks in order to support CME practitioners, funders, and policy makers to develop, implement, and evaluate CME vis-a-vis population health concerns. Evidence: Existing CME conceptual models and conceptions of CME effectiveness require elaboration in order to meet goals of population health improvement. Frameworks for the design, implementation and evaluation of CME consistently reference population health, but do not adequately conceptualize it beyond the aggregation of individual patient health. As a pertinent example, opioid prescribing CME programs use the opioid epidemic to justify their programs, but evaluation approaches are inadequate for demonstrating population health impacts. CME programs that are built to have population health outcomes using frameworks intended primarily for physician performance and patient health outcomes are thus not able to recognize either non-linear associations or negative unintended consequences. Implications: This proposed conceptual framework draws on the fields of clinical population medicine, the social determinants of health, health equity, and philosophies of population health to build conceptual bridges between the CME outcome levels of physician performance and patient health to population health. The authors use their experience developing, delivering, and evaluating opioid prescribing- and poverty-focused CME programs to argue that population health-focused CME must be re-oriented in at least five ways. These include: 1) scaling effective CME programs while evaluating at population health levels; 2) (re)interpreting evidence for program content from a population perspective; 3) incorporating social determinants of health into clinically-oriented CME activities; 4) explicitly building fluency in population health concepts and practices among health care providers and CME planners; and 5) attending to social inequity in every aspect of CME programs.